The impact of integrated practices of lean, green, and social management systems on firm sustainability performance: evidence from Chinese fashion auto-parts suppliers - Wu, Lin; Subramanian, Nachiappan; Abdulrahman, Muhammad; Liu, Chang; Lai, Kee-hung; Pawar, Kulwant (MDPI, 2015)
To better satisfy various stakeholders, firms are seeking integrated practices that can enhance their sustainability performance, also well known as the Triple Bottom Line (3BL). The fashion industry exhibits potential conflicts with the spirit of sustainability because of the waste created by high levels of demand uncertainty and the extant usage of resources in production. Literature suggests that selected stand-alone practices of lean, green, and Corporate Social Responsibility (CSR) management systems have a positive impact on firm sustainability performance. However, how the combination of selected practices from these three management systems impacts the 3BL remains unclear. Based on case studies, we build an integrated sustainable practices model incorporating the most popular lean, green, and social practices and develop propositions for future tests. Our framework suggests the implementation of integrated practices would have a stronger influence on 3BL performance than individual practice implementation.